US Governmental Spending for Disaster-Related Research, 2011–2016: Characterizing the State of Science Funding Across 5 Professional Disciplines. (December 2019) - Kirsch, Thomas D.; Keim, Mark
ABSTRACT: Objective: Disaster-related research funding in the United States has not been described. This study characterizes Federal funding for disaster-related research for 5 professional disciplines: medicine, public health, social science, engineering, emergency management. Methods: An online key word search was performed using the website, www.USAspending.gov, to identify federal awards, grants, and contracts during 2011–2016. A panel of experts then reviewed each entry for inclusion. Results: The search identified 9145 entries, of which 262 (3%) met inclusion criteria. Over 6 years, the Federal Government awarded US 69 325 130 for all disaster-related research. Total funding levels quadrupled in the first 3 years and then halved in the last 3 years. Half of the funding was for engineering, 3 times higher than social sciences and emergency management and 5 times higher than public health and medicine. Ten (11%) institutions received 52% of all funding. The search returned entries for only 12 of the 35 pre-identified disaster-related capabilities; 6 of 12 capabilities appear to have received no funding for at least 2 years. Conclusion: US federal funding for disaster-related research is limited and highly variable during 2011–2016. There are no clear reasons for apportionment. There appears to be an absence of prioritization. There does not appear to be a strategy for alignment of research with national disaster policies.